Nostalgi och samvete: Reflektioner kring nostalgi som strategi i berättelser om staden - Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
People often have strong feelings about changes in the cities. This article deals with questions on how notions of the city can be analysed in relation to nostalgia to enhance the fact that nostalgic views are always constructed in the present, and that they depend on the very changes between past and present which they criticize. Three kinds of nostalgia are discerned. Restorative nostalgia which proposes to rebuild the lost "home" and patch up the memory gaps. Reflective nostalgia which dwells in longing and loss, the imperfect process of longing. To understand the way the informants talk about what they want cities to be — whether they talk about qualities in the past or hopes for the future — I also use Renato Rosaldos term imperialistic nostalgia to indicate how nostalgia can be said to both indicate and effectively hide a responsibility. The tenderness that accompanies the nostalgic feeling draws away the attention from the sometimes fundamental inequality and inherent question of guilt possibly surrounding the remembered event.